Majallat al-Buhuts al-Ilmiyyah wa Kharithah Mafahimuha Fi Qism Ta’lim al-Lughah al-Arabiyyah li al-Marhalah al-Jamiíyyah bi Jamiáh Sunan Kalijaga Yogyakarta wa Jamiáh Ulum al-Qurán bi Wonosobo wa Jamiáh Semarang al-Hukumiyah wa Jamiáh Muhammadiyah bi Yogyakarta - Setiyawan, Agung; Ainin, Moh.; Bahruddin, Uril (Arabiyatuna: Jurnal Bahasa Arab, 2022)
This study departs from the problem of lack of clarity in classification of research areas in Arabic Language Education. This study aims to describe and create a concept map in the research areas of students majoring in Bachelor of Arabic Language Education of UIN Sunan Kalijaga, UNSIQ Wonosobo, UNNES and UMY. This is a descriptive qualitative and quantitative research. Data were collected by way of documentation to be analyzed inductively with content analysis. The qualitative data were analyzed using an interactive analysis, particularly through data reduction, data submission, and conclusion drawing. Meanwhile, the quantitative data were analyzed using a frequency distribution. From the study, it is clear that students taking the Bachelor of Arabic Language Education in several universities in Indonesia mostly conduct their research on the following eighteen topics, namely: learning methods (34.4%), learning media (21.7%), learning materials (10.5%), psycholinguistics (6.1%), syntax (5%), morphology (4.4%) curriculum (3.9%), reading skills (3.3%), science of balaghah (2.8%), translation (2%), learning evaluation (1.1%), dictionary (1.1%), sociolinguistics (1.1%), listening skill (0.5%), speaking skill (0.5%), writing skill (0.5%), phonology (0.5%) and semantics (0.5%). In addition, the concept mapping reveals that teaching and learning serve as the most widely addressed topics in Arabic language education.